2008
DOI: 10.1161/hypertensionaha.107.108985
|View full text |Cite
|
Sign up to set email alerts
|

Lewis K. Dahl Memorial Lecture

Abstract: identified many of the relationships that underlie our current thinking and focus of research on hypertension. Among the first to establish the interactions between salt and hypertension, the realization that genetic factors played a major role in how the kidney responded to salt loads 1 led to development of the genetically predisposed Dahl salt-sensitive rat. His research, although not specifically directed toward aging, recognized that the effects of high-salt diets were not necessarily immediate. In fact, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 65 publications
2
19
0
1
Order By: Relevance
“…There is strong evidence that ACE inhibitors or AT 1 receptor antagonists have a profound impact on the treatment of cardiovascular disease. Emerging data suggest that the RAS may influence the course of other pathologies, including cancer, diabetes, pulmonary injury and aging (25,26). Indeed, AT 1 receptor knockout mice exhibit a significant increase in life span when maintained on a normal chow/caloric diet, which supports earlier studies on the protective effects of ACE inhibitors in aging rats (2,26,28,33).…”
Section: Angiotensin Receptor Regulation In Fetal Programmingsupporting
confidence: 73%
See 1 more Smart Citation
“…There is strong evidence that ACE inhibitors or AT 1 receptor antagonists have a profound impact on the treatment of cardiovascular disease. Emerging data suggest that the RAS may influence the course of other pathologies, including cancer, diabetes, pulmonary injury and aging (25,26). Indeed, AT 1 receptor knockout mice exhibit a significant increase in life span when maintained on a normal chow/caloric diet, which supports earlier studies on the protective effects of ACE inhibitors in aging rats (2,26,28,33).…”
Section: Angiotensin Receptor Regulation In Fetal Programmingsupporting
confidence: 73%
“…Emerging data suggest that the RAS may influence the course of other pathologies, including cancer, diabetes, pulmonary injury and aging (25,26). Indeed, AT 1 receptor knockout mice exhibit a significant increase in life span when maintained on a normal chow/caloric diet, which supports earlier studies on the protective effects of ACE inhibitors in aging rats (2,26,28,33). Our studies in older adult sheep also revealed evidence for an altered balance in the nuclear expression of ANG receptors, as well as the functional responses of the ANG II-AT 1 receptor axis (40).…”
Section: Angiotensin Receptor Regulation In Fetal Programmingmentioning
confidence: 99%
“…Recent studies have suggested their potential role in the activation of inflammatory mechanisms associated with age-related vascular and renal damage. For one thing, Ang II signaling increases with aging (Basso et al 2005;Diz and Lewis 2008). For another, suppression of Ang II signaling attenuates the development of age-related vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that it is also a potent mediator in the activation of inflammatory mechanisms during age-related vascular and renal disease (Basso et al 2005;Diz and Lewis 2008). The use of Ang II antagonists in the treatment of these agerelated diseases provides strong support for its proinflammatory role (de Cavanagh et al 2003(de Cavanagh et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is also associated with activation of local tissue RAS and systemic RAS blockade prevents other age-related changes; this strongly suggests that mechanisms involving the blockade of local-tissue RAS contribute to the protective effects of systemic RAS blockade during aging (13). Importantly, other components of the local RAS in vessel walls such as angiotensin-converting enzyme (ACE) are also upregulated during atherosclerosis, and a high abundance of Ang II has been shown in atherosclerotic plaques as well as in hypercholesterolemia (3,14,15).…”
mentioning
confidence: 99%